2002
DOI: 10.2337/diacare.25.8.1331
|View full text |Cite
|
Sign up to set email alerts
|

Total Sialic Acid and Associated Elements of the Metabolic Syndrome in Women With and Without Previous Gestational Diabetes

Abstract: OBJECTIVE -Inflammatory markers predict type 2 diabetes and relate to the metabolic syndrome. Gestational diabetes mellitus (GDM) predicts type 2 diabetes and may be part of this syndrome. To examine the association of inflammatory markers with GDM, we investigated total sialic acid (TSA) in women with and without previous GDM.RESEARCH DESIGN AND METHODS -All women with GDM and a random sample of women from one center of the Brazilian Study of Gestational Diabetes were invited to return 7 years after their ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…As NAFLD is closely associated with the MS, the relation between SA and MS may indirectly support the link between SA and NAFLD. This result was consistent with the report from Sriharan et al [30 ]and Yerlikaya et al [31], who also observed that serum SA levels was strongly associated with the components of MS from studies of different designs. Notably, our results first demonstrated that serum SA levels were elevated and showed a positive correlation with BMI, SBP, DBP, serum TG and FPG concentrations in NAFLD subjects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As NAFLD is closely associated with the MS, the relation between SA and MS may indirectly support the link between SA and NAFLD. This result was consistent with the report from Sriharan et al [30 ]and Yerlikaya et al [31], who also observed that serum SA levels was strongly associated with the components of MS from studies of different designs. Notably, our results first demonstrated that serum SA levels were elevated and showed a positive correlation with BMI, SBP, DBP, serum TG and FPG concentrations in NAFLD subjects.…”
Section: Discussionsupporting
confidence: 83%
“…A vast body of literature addressed that SA-mediated numerous biological functions including metabolic regulation of glycoproteins and lipids, cellular adhesion and molecular signaling pathway, involving various pathophysiologic activities [7,8,9]. Over the past few years, clinical data confirmed the association between circulating SA levels and MS [10,11]. Serum SA levels are often elevated in subjects with MS and serum SA is also a potential risk factor for cardiovascular disease [12].…”
Section: Introductionmentioning
confidence: 96%
“…Serum triglycerides, insulin, and glucose were measured using standardized laboratory techniques as described in reference [19]. Plasma sialic acid was quantified using an enzymatic method (Boehringer Mannheim, Lewes, Sussex, UK) on a Roche Cobas Fara analyzer (Roche, Basel, Switzerland) [20].…”
Section: Methodsmentioning
confidence: 99%
“…In the years after their index pregnancy, women with a history of gestational diabetes have an increased prevalence of several cardiometabolic derangements, including traditional vascular risk factors (e.g., type 2 diabetes, hypertension, dyslipidemia, obesity and metabolic syndrome 2,[16][17][18][19][20] impaired endothelium-dependent vasodilatation and subclinical atherosclerosis 22,24,25 ). Thus, it is not surprising that gestational diabetes has been reported to be associated with increased risk of future cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%